THE ROLE OF AI IN DEMOCRATIZING VISUAL STORYTELLING - Talati, Bijal Jigar; Jain, Garima; Brar, Manvinder; K Prakash; Yadav, Veerendra; J P Yadav; Mundada, Kapil (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The fast development of artificial intelligence turned visual storytelling into a more approachable, inclusive and participatory creative action. Historically, visual narratives were only done well by specialized artistic skills and costly equipment, and a barrier of experience in production that made visual media communication only available to a few. This can be minimized by AI-enhanced technologies like generative image models, style-transfer systems, multimodal storytelling systems, and automated editing pipelines which allow users with diverse backgrounds to tell captivating visual stories with more ease than ever before. They favor ideation, the structuring of narrative, composition of a scene, and aesthetic polishing, allowing individuals with no formal training in art to visualize themselves and experiment in a creative way. Also, since AI personalises visual content based on cultural and emotional subtexts and user-specific intentions, it creates more genuine and meaningful storytelling. It also facilitates usability with voice-to-image synthesis, user-friendly interfaces to creators with limited abilities and language-neutral narrative editors. AI promotes creative confidence in learning settings, which allows students to cycle quickly and visualize abstract ideas. On a societal level, AI democratizes the process by enabling marginalized groups to get new channels to conserve narratives, rebrand traditions, and recount lived experiences on the digital realms. Along with these developments, such aspects of ethics as authorship, originality, bias, and responsible deployment are also of critical importance. On the whole, AI is a radical power that broadens the range of creators, the format of stories, and those whose voices are heard within the visual storytelling system.